Fifteen Uninterrupted Years of Maternal Mortality Findings from a Tertiary Care Centre - Rana, Ashma; Shrestha, Junu; Maskey, Suvana; Kaudel, Sudeep; Shrestha, Prashant; Katuwal, Neeta; Paudyal, Pooja; Rana, Apariharya (Journal of College of Medical Sciences-Nepal, 2021)
Introduction Maternal mortality reflects reproductive health status and availability of good health care facilities at different levels of the healthcare system at a given period, influenced by globally adopted safe motherhood policies. The leading causes of maternal death in Nepal mainly comprise of hemorrhage, eclampsia, abortion-related complications, gastroenteritis and anemia. Although a declining trend has been noted in Nepal it has yet to meet the target set by the Sustainable Development Goal (SDG) 3.1 of reducing the global MMR to less than 70 maternal deaths per 100,000 live births by 2030. Methods A cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Tribhuvan University Teaching Hospital (TUTH) from 1st Baisakh 2055- 30th Chaitra 2069 (15th April 1998- 14th April 2013). The study period of 15 years was divided into three parts, five years each: 2055-59 (14th April 1998-April 13th 2003) ; 2060-64 (14th April 2003- April 12th 2008) and 2065-69 (April 13th 2008 –April 12th 2013). MM was filled in Performa, discussed in morning conference and MM audit, computerized, analyzed, presented quarterly and yearly. Annual Maternal Mortality Ratio (MMR) expressed as MMR per 100,000 live births is calculated by dividing recorded (or estimated) maternal deaths by total recorded (or estimated) live births in the same period and multiplying by 100,000. Results Total MM/maternal mortality ratio (MMR) in the first, mid and last five years were 39 (270 %); 37 (212% ) and 37 (188%) respectively giving overall total MM/MMR 113 (223.5%) attributing to Direct: 55 ( 48.6%), Indirect: 44 (38.9%) and Non maternal deaths: 14 (12.3%). Predominating cause of MM in the first/mid/last five years were sepsis and infective hepatitis each (17.6%) and PPH (18.5 %). While SP/E were almost same over the years, in decreasing trend were hepatitis and puerperal sepsis but in rising trend was PPH and criminally induced abortion (10.6%). The number of maternal death has not changed much, the median age in each five years is surprisingly similar, set at 25 years and the adolescents who died were not very different in every five years. It’s unfortunate that many primigravida died during this period which is a matter of concern. Conclusions Maternal mortality stresses the impact of timely health seeking behaviour and health providers making provision of prompt adequate services and referral to help so that all Nepalese mothers, especially the young and first-time pregnant thrive. Keywords: infective hepatitis, maternal mortality, maternal mortality ratio, PPH, sepsis.